A Phono-Stylistic Analysis of Langston Hughes’ Poem “Harlem” - Rangkuti, Rahmadsyah; Tannada, Susanty (JL3T (Journal of Linguistics, Literature and Language Teaching), 2024)
This research was utilized stylistic analysis tools at the phonological level in the poem titled “Harlem” by Langston Hughes. By leveraging the collective cultural scheme of the Harlem Renaissance, Hughes establishes a connection with the reader, eliciting specific cultural and emotional reactions. The study will be conducted using a qualitative method, followed by organizing the research data into a table and analyzing it by identifying dominant consonants and vowels. The research findings reveal a correlation between the dominant sounds and implicit themes in the poem. Surprisingly, the dominant sounds which is consonant give rise to words such as ‘tear’ and ‘star’, which are related to the theme of the Harlem poem. Both words obtained in this study strengthen the message and emotions conveyed by Hughes regarding the feelings of black individuals. In undertaking this research, it aids researchers in understanding the purpose, intent, and even the style of the author in creating the poem. In this particular poem, Hughes avoids repetition of themes but conveys the feelings of black individuals implicitly. This research contributes to deepening the understanding of stylistic elements at the phonological level and fosters an appreciation for a literary work.